2020
DOI: 10.1177/1078155220920690
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of hemorrhagic cystitis after cyclophosphamide therapy with or without mesna: A cohort study and comprehensive literature review

Abstract: Background Cyclophosphamide is an alkylating agent associated with significant toxicities, most importantly hemorrhagic cystitis. Many approaches including mesna use were established to reduce this toxicity. However, data on mesna efficacy are conflicting. Objective To investigate the incidence of hemorrhagic cystitis in patients receiving cyclophosphamide therapy with or without mesna. Methods A retrospective chart review was done on all adult patients receiving cyclophosphamide therapy with or without mesna … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Mesna is an adjuvant used clinically with cyclophosphamide to reduce hemorrhagic cystitis. However, a recent paper reviewed 718 patients' cases and found that the mesna group had a greater incidence of cyclophosphamide-induced hemorrhagic cystitis compared to the non-mesna group (Almalag et al, 2021). Our study demonstrates the protective effect of the P2X7 receptor inhibition on the urothelium in an ex-vivo acrolein model of bladder cystitis.…”
Section: Discussionmentioning
confidence: 52%
“…Mesna is an adjuvant used clinically with cyclophosphamide to reduce hemorrhagic cystitis. However, a recent paper reviewed 718 patients' cases and found that the mesna group had a greater incidence of cyclophosphamide-induced hemorrhagic cystitis compared to the non-mesna group (Almalag et al, 2021). Our study demonstrates the protective effect of the P2X7 receptor inhibition on the urothelium in an ex-vivo acrolein model of bladder cystitis.…”
Section: Discussionmentioning
confidence: 52%
“…One of the most serious side effects of using cyclophosphamide is the risk of causing hemorrhagic cystitis [ 30 ]. The mechanism of this complication is associated with the liver metabolism of cyclophosphamide (which is a prodrug), resulting in the formation of active metabolites: phosphoramide mustard and the toxic acrolein.…”
Section: Chemotherapymentioning
confidence: 99%
“…The recommended total dose of mesna in humans is, in most cases, 60% (w/w) of the CPX dose given in three divided doses (15-30 min before, 4 h and 8 h after the oxazaphosphorine), but may be increased up to 160% of the CPX dose in four divided doses or even up to 320% of the daily post-transplant cyclophosphamide dose [5,41,43]. However, the efficacy of mesna use is currently being discussed, especially considering the CPX-induced urinary complications in the treatment of chronic diseases [15,16]. Additionally, mesna may cause some skin and systemic hypersensitivity-like-reactions, but it is sometimes difficult to distinguish these from the adverse effects of the basic anticancer protocol [41,44].…”
Section: Discussionmentioning
confidence: 99%
“…The postulated mechanism of mesna, a sulfhydryl compound, is that it binds the methyl group of acrolein which leads to the formation of thioether, which is non-toxic, and does not trigger the inflammatory process [12,13]. Recently, the efficacy of mesna in clinical practice has been widely discussed and some trials, as well as the literature overview, indicate great differences in the conclusions drawn [14][15][16]. Therefore, there is still a great need to look for new compounds, which may prevent CPX-induced cystitis decreasing the risk of severe hemorrhagic outcomes and additionally may prevent kidney injury.…”
Section: Introductionmentioning
confidence: 99%